2006
DOI: 10.2135/cropsci2005.10-0378
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Atmospheric Carbon Dioxide and Weed Populations in Glyphosate Treated Soybean

Abstract: Although rising atmospheric carbon dioxide (CO 2 ) is known to stimulate the growth of agronomic weeds, the impact of increasing CO 2 on herbicide efficacy has not been elucidated for field-grown crops. Genetically modified soybean [Glycine max (L.) Merr.] (i.e., Round-up Ready soybean) was grown over a 2-yr period at ambient and projected levels of atmospheric carbon dioxide (CO 2 , 250 mmol mol 21 above ambient), with and without application of the herbicide, glyphosate [N-(phosphonomethyl)glycine], to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 15 publications
2
38
0
2
Order By: Relevance
“…At the whole plant level, changes in allometry and phenology can influence time to flowering, flower number and pollen production (Ziska and Bunce 2006). At the level of community, plant competition may be altered with a resultant change in species number or species diversity (Ziska and Goins 2006). Overall, these changes could alter invasive insect-host interactions by either altering the insects feeding behavior or by altering plant defenses.…”
Section: Invasive Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the whole plant level, changes in allometry and phenology can influence time to flowering, flower number and pollen production (Ziska and Bunce 2006). At the level of community, plant competition may be altered with a resultant change in species number or species diversity (Ziska and Goins 2006). Overall, these changes could alter invasive insect-host interactions by either altering the insects feeding behavior or by altering plant defenses.…”
Section: Invasive Insectsmentioning
confidence: 99%
“…There are initial studies indicating a potential decline in chemical efficacy with rising [CO 2 ] and/or temperature for some weeds (Ziska and Goins 2006;Archambault 2007). For example, there are data for two invasive agricultural weeds, Canada thistle and quackgrass (Elytrigia repens), demonstrating that elevated levels of carbon dioxide can reduce herbicide efficacy (Ziska and Teasdale 2000;).…”
Section: Invasive Species Management: Preparing For the Futurementioning
confidence: 99%
“…Therefore it seems likely that any resource increase is likely to stimulate the growth of one or more weed species in a cropweed mix than the crop. Recent data for a soybean/weed system in fact, indicate C 3 annuals (e.g., lambsquarters, Chenopodium album) are favored by natural selection with prolonged exposure to increased CO 2 , leading to increased competition with soybean (Ziska and Goins 2006a). …”
Section: Weed Responses To Comentioning
confidence: 99%
“…Unfortunately, there are also an increasing number of studies (Ziska et al 1999(Ziska et al , 2004Ziska and Teasdale 2000;Ziska and Goins 2006a) that demonstrate a decline in chemical efficacy with rising CO 2 per se. Given the evidence from field and laboratory trials, it appears that declining efficacy of herbicides with increasing CO 2 is very likely to affect the environmental and economic cost of pesticide usage (Ziska et al 1999;Ziska and Teasdale 2000).…”
Section: Implications For Control and Managementmentioning
confidence: 99%
“…Hitherto studies concerned the effect of increased CO 2 on the growth and yields of some crops. In most studies it was concluded that yields of some crops such as maize, soybean, wheat and rice are increased in response to elevated CO 2 (Alberto et al, 1996;Ziska and Bunce 1997;Ziska and Goins 2006;Patel et al 2008;Erbs et al, 2009). Some other studies concerned however, the effects of CO 2 increase on the growth and competition ability of weeds and their results showed that weed growth can be improved by elevated CO 2 as well (Ziska and Bunce 1997;Ziska 2002;Pandey et al, 2003).…”
Section: Introductionmentioning
confidence: 99%